2015
DOI: 10.1002/ajmg.a.37073
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloepiphyseal dysplasia congenita caused by double heterozygous mutations in COL2A1

Abstract: Spondyloepiphyseal dysplasia congenita (SEDC) is a group of rare inherited chondrodysplasias characterized by short stature, abnormal epiphyses, and flattened vertebral bodies. SEDC is usually caused by substitution of glycine residue with another amino acid in the triple helical domains of alpha 1 chains, which consist of type II collagen (COL2A1). Herein, we describe a unique case of SEDC with mild coxa vara (SEDC-M) caused by double de novo COL2A1 mutations located on the same allele. One mutation, p.G504S,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…In the data obtained from 663 probands with COL2A1 mutations, 535 and 114 cases of mutations were located in the CDS and intron regions of the COL2A1 , respectively. It is noteworthy that one patient with SEDC carried two mutations (p.Gly504Ser and p.Gly612Ala) on the same allele . This case was characterized by a more severe phenotype compared with previously reported cases involving a single p.Gly504Ser mutation …”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In the data obtained from 663 probands with COL2A1 mutations, 535 and 114 cases of mutations were located in the CDS and intron regions of the COL2A1 , respectively. It is noteworthy that one patient with SEDC carried two mutations (p.Gly504Ser and p.Gly612Ala) on the same allele . This case was characterized by a more severe phenotype compared with previously reported cases involving a single p.Gly504Ser mutation …”
Section: Resultsmentioning
confidence: 52%
“…It is noteworthy that one patient with SEDC carried two mutations (p.Gly504Ser and p.Gly612Ala) on the same allele. 27 This case was characterized by a more severe phenotype compared with previously reported cases involving a single p.Gly504Ser mutation. 28 Interestingly, according to the analysis of the variant position and severity of the phenotype (Figure 2) (the classification criteria of severity were selected from Deng et al 52 ), we found two most likely genotypephenotype correlations.…”
Section: Variant Locations Related To Phenotypesmentioning
confidence: 59%
“…We have previously reported OA-like changes in a mouse model that bears a mutation in the Col2a1 gene, similar to that found in humans, that behaves as a recessive mutation resulting in no obvious phenotype in the heterozygote [9]. The mouse mutation was named spondyloepiphesial dysplasia congenita (sedc) [10] because when homozygous it produces features that resemble the most common clinical phenotypes of SED congenita in humans [11]. Thus in both mouse and human it is known that collagen gene mutations that lead to a wide variety of disorders of the skeletal system can also lead to premature osteoarthritis.…”
mentioning
confidence: 80%
“…In this case, both mutations were located in the coding sequence for the triple helix domain and a severe phenotype was also reported. 16 An additional mutation was described in another Japanese patient with SMD-A phenotype who presented with short stature, severe leg deformity, severe genu valgum, myopia, and hearing impairment. This patient had a heterozygous missense mutation located in the triple helical domain (p.G861V) in COL2A1.…”
Section: Discussionmentioning
confidence: 99%